2018
DOI: 10.1007/s00128-018-2278-8
|View full text |Cite
|
Sign up to set email alerts
|

Levels of PCDD/Fs, PBDEs, and PBDD/Fs in Breast Milk from Southern Taiwan

Abstract: This study investigates the congener-specific concentrations of polychlorinated dibenzo-p-dioxins/furans (PCDD/Fs), polybrominated dibenzo-p-dioxins/furans (PBDD/Fs), and polybrominated diphenyl ethers (PBDEs) in 25 breast milk samples from southern Taiwan. Most investigated congeners in Taiwanese breast milk are detectable except for PBDD/Fs. The geometric means of PCDD/Fs and PBDEs in the breast milk are 2.44 pg WHO-TEQ/g lipid and 2810 pg/g lipid. Several PCDD/F and PBDE congeners were highly correlated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…PBDD/Fs are brominated dioxins found as impurities of PBDEs and formed during the incineration and degradation of brominated chemicals. 62 Similar to previous reports, 63,64 we observed low DFs for PBDD/Fs. Therefore, the thyroiddisrupting properties of these chemicals were not assessed here.…”
Section: Discussionsupporting
confidence: 90%
“…PBDD/Fs are brominated dioxins found as impurities of PBDEs and formed during the incineration and degradation of brominated chemicals. 62 Similar to previous reports, 63,64 we observed low DFs for PBDD/Fs. Therefore, the thyroiddisrupting properties of these chemicals were not assessed here.…”
Section: Discussionsupporting
confidence: 90%
“…Geometric mean values in this study (2016-18) reported by Hernández et al [22] , 2020, (GM PCDD/Fs + dl-PCB TEQ; 4.42 ng kg -1 ) in the Spanish BETTERMILK study for samples collected in 2015. Irish values in this study (PCDD/Fs + dl-PCB TEQ GM 4.5 ng kg -1 ) are comparable to values reported in the fourth and fifth WHO UNEP survey for less industrialised countries and countries in the southern hemisphere [14] and are much lower than those reported for mainland Europe including Italy (AM value; 13.4 ng kg -1 ) [26] and France (10.74 ng kg -1 ) [31] . They are also less than those reported in the last Irish study for samples collected in 2009-2010 (AM value; 9.66 ng kg -1 ) [15] .…”
Section: Discussionsupporting
confidence: 77%
“…A Vietnamese study (Tue et al, 2014) on dioxin-like compounds in 25 human milk samples from women working at three e-waste recycling sites, was only able to detect 2,3,7,8-TBDF at levels of < 0.49 to 1.4 pg/g lipid. Similarly, another Vietnamese study (Chen et al, 2018) reported undetectable levels from 25 breast milk samples from southern Taiwan.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 91%